Mechanical properties of styrene butadiene rubber toughened graphene reinforced polystyrene - N. F., Ab Ghani; M. S. Z., Mat Desa; M., Yusop; M., Bijarimi; A., Ramli; M. F., Ali (IOP Publishing, 2020)
In this study, styrene butadiene rubber was used for toughened polystyre/graphene nanoplatelets (PS/GNP) nanocomposites. The objective of this research is to determine the effect of styrene butadiene rubber (SBR) contents on the toughness of PS/GNP nanocomposites. In order to achieve the objectives of the research PS/GNP nanocomposites were prepared with various SBR content styrene butadiene rubber content, while the contents of GNP were fixed at 0.5 wt%. The PS/GNP/SBR nanocomposites were prepared by melt blending technique. Mechanical properties of SBR toughened PS/GNP nanocomposites showed a decrement of toughness and tensile strength with increasing content of SBR. SEM study shows that the rubber dispersed uniformly within the blends with polystyrene nanocomposites. SEM results show that the polystyrene mixed with graphene nanoplatelets (PS/GNP) had the smooth surface compare to samples have toughened with styrene butadiene rubber. The mechanical properties of PS/GNP nanocomposites with contain of 15 wt% of SBR shown the best of toughening effect.